2014
DOI: 10.14814/phy2.12007
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of a field technique for sweat Na+and K+analysis during exercise in a hot-humid environment

Abstract: This study compared a field versus reference laboratory technique for extracting (syringe vs. centrifuge) and analyzing sweat [Na+] and [K+] (compact Horiba B‐722 and B‐731, HORIBA vs. ion chromatography, HPLC) collected with regional absorbent patches during exercise in a hot‐humid environment. Sweat samples were collected from seven anatomical sites on 30 athletes during 1‐h cycling in a heat chamber (33°C, 67% rh). Ten minutes into exercise, skin was cleaned/dried and two sweat patches were applied per anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 27 publications
0
47
0
Order By: Relevance
“…No study, to the author’s knowledge, has directly compared all methods, but a synopsis of the literature suggests that sweat [Na + ] is generally highest with conductivity and FP, intermediate with ISE, and lowest with IC. For example, in separate studies, conductivity produced approximately 6% higher sweat [Na + ] values than FP [124], FP values were approximately 20% higher than ISE [18] and IC [96], and ISE values were approximately 4% [125] and approximately 10% [126] higher than IC.…”
Section: Methodological Sources Of Variability In Sweating Rate and Smentioning
confidence: 99%
See 4 more Smart Citations
“…No study, to the author’s knowledge, has directly compared all methods, but a synopsis of the literature suggests that sweat [Na + ] is generally highest with conductivity and FP, intermediate with ISE, and lowest with IC. For example, in separate studies, conductivity produced approximately 6% higher sweat [Na + ] values than FP [124], FP values were approximately 20% higher than ISE [18] and IC [96], and ISE values were approximately 4% [125] and approximately 10% [126] higher than IC.…”
Section: Methodological Sources Of Variability In Sweating Rate and Smentioning
confidence: 99%
“…ISE techniques, while a measure of ion activity rather than a direct measure of concentration, are considered acceptable for CF diagnosis [122, 127, 133]. Studies measuring sweat [Na + ] have found that ISE (via a compact Na + analyzer; HORIBA Scientific, Irivine, CA, USA) has similar reliability to that of IC (CVs approximately 1–4% for both methods) [125, 126]. These studies also reported that compared with IC, the ISE technique produced sweat [Na + ] values with a mean bias of approximately 2–4 mmol/L (or approximately 4–10%) [125, 126].…”
Section: Methodological Sources Of Variability In Sweating Rate and Smentioning
confidence: 99%
See 3 more Smart Citations